Influence of N2O/TEGa Ratio on Deposition of β-Ga2O3 Films and Performance of Au-β-Ga2O3-Au Solar-Blind Photodetectors. (3rd May 2021) - Huang, Chun-Ying; Liu, Yen-Yang; Lin, Pei-Te; Lin, Guan-Yu; Chou, Cheng-Ping; Liao, Pei-Chun; Hsu, Feng-Hsuan; Peng, Yu-Hsiang; Huang, Zi-Ling; Lin, Tai-Yuan; Gong, Jyh-Rong
Abstract : In this study, a series of β -Ga2 O3 films are prepared by using triethylgallium (TEGa) and nitrous oxide (N2 O) as precursors to explore the effect of N2 O/TEGa ratio on the characteristics of β -Ga2 O3 films. A metal/semiconductor/metal (MSM)-type solar blind ultraviolet (UV) photodetector (PD) is fabricated using as-prepared β -Ga2 O3 film. It is found that an increment of N2 O/TEGa ratio tends to suppress the oxygen vacancies in β -Ga2 O3 film so the device performance can be significantly improved. This work gives a deep insight into the impact of TEGa/N2 O ratio for depositing β -Ga2 O3 on the film quality, the surface morphology, the chemical composition and the device performance for UV PDs.